Fourteen days of etoricoxib 60 mg improves pain, hyperalgesia and physical function in individuals with knee osteoarthritis: a randomized controlled trial. Issue 11 (November 2017) - Moss, P.; Benson, H.A.E.; Will, R.; Wright, A.
Summary: Objective: Mounting evidence points to the heterogeneity of osteoarthritis (OA) pain, increasing the need for more comprehensive assessment of the efficacy of standard interventions. This study investigated whether 14 days of the selective Cox-2 inhibitor etoricoxib (60 mg/day) would modify self-report of pain intensity and quality, and physical measures of hyperalgesia and function in individuals with knee OA. Design: This double-blind placebo-controlled trial included 80 community-recruited volunteers with painful knee OA (≥3/10 VAS), randomly allocated to Active or Placebo groups. Self-report measures of pain, stiffness, function Western Ontario and McMaster University Osteoarthritis Index (WOMAC) and pain quality (PainDETECT, Pain Quality Assessment Scale [PQAS]) and physical measures of locomotion and local (knee) and widespread (elbow) hyperalgesia were assessed at Days 0, 4 and 14. Repeated Measures ANOVA analysed group differences. Results: Significant group × time interaction effects were found for all measures of pain (all p  < 0.001), with WOMAC pain sub-score improving by 30.7% by Day 14 and index knee mechanical hyperalgesia improving by 32.6%, whilst Placebo group values worsened. Both self-report and physical tests of function improved ( p  < 0.001– p  = 0.006): WOMAC-function by 28.4%, sit-to-stand and walk time by 13%, pain during locomotion tasks by 12.4–32.6%. Pain quality also significantly improved for the Active and declined for the Placebo group ( p  < 0.001): PainDETECT score reduced by 23.6% and PQAS paroxsysmal and surface sub-scores by 36.9% and 29.4%. There were also significant improvements in local cold hyperalgesia and widespread mechanical hyperalgesia (10–13.8%). Conclusion: Just 14 days of etoricoxib significantly improves pain intensity and quality, function and local and widespread hyperalgesia, measured by both self-report and physical tests.